Excision of a giant pseudo-pancreatic cyst masquerading as ascites in young patient: a case report - Nelson, Thirugnanasambandam; Vargheese, Saji; Patra, Satya Ranjan; Saha, Arnab (International Surgery Journal, 2020)
Pancreatic pseudocysts are diagnosed more frequently due to increased usage of imaging techniques. A pseudocyst with diameter of 10 cm is defined as giant cyst. Larger and symptomatic pseudocysts require intervention while cysts upto 6 cm can be managed conservatively. A 16 year old young patient presented with abdominal pain, progressive abdominal distension, and breathlessness for 15 days. On examination, patient had tense distended abdomen with gross ascites. His vitals showed tachycardia, hypotension and tachypnea. After resuscitation, ultrasound showed gross ascites with moving echoes and contrast-enhanced computed tomography (CECT) abdomen showed similar findings. Patient underwent multiple therapeutic tapping of ascitic fluid but no significant improvement. Diagnostic laparoscopy showed giant pseudo pancreatic cyst extending from diaphragm to the pelvis with necrotic material. Patient underwent exploratory laparotomy, drainage of necrotic material with excision of giant pseudocyst and roux-en-y pancreaticojejunostomy. Post operatively patient had an uneventful recovery. Giant pancreatic pseudocysts are unusual and early management is required. Some experts considered external drainage is safer than cystogastrostomy. We suggest early diagnosis and surgical excision is feasible for a giant pancreatic pseudocyst. However, endoscopic drainage can be considered in some instances.